Tiktok Usage's Linguistic Effect on a Preschooler's Language Development: A Qualitative Case Study - Nadya Elchaira; Alemina Br. Perangin-angin; Rusdi Noor Rosa (Journey: Journal of English Language and Pedagogy, 2024)
Tik Tok is incredibly popular across all age groups, including young children. Its attractiveness, use, and accessibility have a big influence on how children perceive linguistic exceptions when using the app. The focus on this study is to investigate the impact of TikTok on the linguistic development of a five-year-old child. This study utilizes a case study methodology and a qualitative research strategy. In this study, interviews and observations are the methods used to collect data. Feiza Elhayatein, a five-year-old child who watches Tik Tok videos at times, is the study's subject. The study's findings indicated that Feiza had a greater capacity for language use, but parents should exercise greater caution in this regard. Feiza's parents do need to set limits and restrictions for her Tiktok video consumption, even though this application may help her learn the language.